2022
DOI: 10.3889/oamjms.2022.8445
|View full text |Cite
|
Sign up to set email alerts
|

How Do They Feel at the First Line During the Covid Outbreak: A Survey among Indonesian Nurses

Abstract: AIM: This descriptive survey study is conducted to examine the nurses’ perceived occupational safety as a front line during the pandemic period in Aceh Province, Indonesia METHODS: This research used a cross-sectional study design. The study was conducted in all districts/cities in the Aceh province. Sample in this study amounted to 199 respondents, collected using a snowball sampling technique. The developed questionnaire consists of respondents’ demographic data and Nurse Occupational Safety Questionnaire,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…According to Mohaithef's (2020) study, 65.4% of nurses demonstrated appropriate hand hygiene practices, while 10.3% showed inappropriate practices. These results suggest that despite positive attitudes, some nurses do not always follow good hand hygiene practices (Putra et al, 2022b). Moreover, the study found that women (88%) had significantly higher rates of good hand hygiene practices than men (44%) (Mohaithef, 2020).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…According to Mohaithef's (2020) study, 65.4% of nurses demonstrated appropriate hand hygiene practices, while 10.3% showed inappropriate practices. These results suggest that despite positive attitudes, some nurses do not always follow good hand hygiene practices (Putra et al, 2022b). Moreover, the study found that women (88%) had significantly higher rates of good hand hygiene practices than men (44%) (Mohaithef, 2020).…”
Section: Discussionmentioning
confidence: 83%
“…Ensuring proper hand hygiene is a critical precaution individuals can take to safeguard themselves against COVID-19 and its transmission during the pandemic (Putra et al, 2022b). It serves as a fundamental component of infection control, acting as the first line of defense against the spread of harmful microorganisms (Jacob and Srijayanth, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation